Pengenalan Konsep Dasar dan Praktikum Kimia Sederhana Pada Siswa Dan Guru di SMA Negeri 42 Maluku Tengah - Pada, Semuel Simra; Sutapa, I Wayan (Universitas Mataram, 2024)
Community service is an integral part of the Tri Dharma of Higher Education, playing a crucial role in the development of knowledge and the improvement of societal well-being. As a tangible manifestation of this responsibility, the faculty members of the Chemistry Department at FMIPA, Universitas Pattimura, conducted a community service program titled